The influence of heavy metals on toxicogenetic damage in a Brazilian tropical river. (October 2017) - Matos, Leomá A.; Cunha, Ana C.S.; Sousa, Aline A.; Maranhão, Jéssica P.R.; Santos, Nathanyel R.S.; Gonçalves, Matheus de M.C.; Dantas, Sandra M.M. de M.; Sousa, João M. de C. e; Peron, Ana P.; Silva, Felipe Cavalcanti Carneiro da; Alencar, Marcus V.O.B. de; Islam, Md. Torequl; et al.
Abstract: Anthropogenic activities in tropical rivers favor the eutrophication process, which causes increased concentration of heavy metals. The presence and bioaccumulation of metals are directly related to the presence of genotoxic damage in aquatic organisms. Thus, we evaluated the presence of heavy metals (Fe, Zn, Cr, Cu and Al) and performed toxicogenetic tests in surface (S) and bottom (B) of water samples of the Poti river (Piaui/Brazil). Cytotoxicity and genotoxicity tests were performed in Allium cepa, and micronucleus (MN) and comet assay were performed in Oreochromis niloticus. The chemical analysis showed concentrations above the limit for Cu, Cr, Fe and Al according to Brazilian laws, characterizing anthropogenic disturbance in this aquatic environment. Toxicogenetic analysis presented significant cytotoxic, mutagenic and genotoxic effects in different exposure times and water layers (S and B), especially alterations in mitotic spindle defects, MN formations, nuclear bud and DNA strand breaks. Correlations between Fe and cytotoxicity, and Al and mutagenicity were statistically significant and point out to the participation of heavy metals in genotoxic damage. Therefore, Poti river water samples presented toxicogenetic effects on all bioindicators analyzed, which are most likely related to heavy metals pollution. Highlights: Poti river carries polluted water. Poti river water exhibited genotoxic effects in Oreochromis niloticus. Heavy metal-induced significant toxic effects.